Accidental radioisotope burns - Management of late sequelae - Varghese Bipin; Thomas Shaji; Nair Balakrishnan; Mathew P; Sebastian Paul (Indian Journal of Plastic Surgery)
Accidental radioisotope burns are rare. The major components of radiation injury are burns, interstitial pneumonitis, acute bone marrow suppression, acute renal failure and adult respiratory distress syndrome. Radiation burns, though localized in distribution, have systemic effects, and can be extremely difficult to heal, even after multiple surgeries. In a 25 year old male who sustained such trauma by accidental industrial exposure to Iridium192 the early presentation involved recurrent haematemesis, pancytopenia and bone marrow suppression. After three weeks he developed burns in contact areas in the left hand, left side of the chest, abdomen and right inguinal region. All except the inguinal wound healed spontaneously but the former became a non-healing ulcer. Pancytopenia and bone marrow depression followed. He was treated with morphine and NSAIDs, epidural buprinorphine and bupivicaine for pain relief, steroids, antibiotics followed by wound excision and reconstruction with tensor fascia lata(TFL) flap. Patient had breakdown of abdominal scar later and it was excised with 0.5 cm margins up to the underlying muscle and the wound was covered by a latissimis dorsi flap. Further scar break down and recurrent ulcers occurred at different sites including left wrist, left thumb and right heel in the next two years which needed multiple surgical interventions.